Dasar-dasar hukum pidana di Indonesia / P.A.F. Lamintang ; editor Ihsan, Tarmizi - LAMINTANG, P.A.F.; Franciscus Theojunior Lamintang; Ihsan; Tarmizi (Sinar Grafika, 2014)
xiii, 770 hlm. ; 23 cm (3 eks.)